Organizational Capacity and Implementation of Internal Quality Assurance: an Administrative Study on Vocational Schools in Makassar City - Arhas, Sitti Hardiyanti; Nasir, Nasir; Jamaluddin, Jamaluddin (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study examines the implementation of the Internal Quality Assurance System (Sistem Penjaminan Mutu Internal; SPMI) as a public policy instrument in the management of vocational education across five vocational high schools in Makassar, Indonesia. The analysis focuses on how the PPEPP cycle (Penetapan, Perencanaan, Pelaksanaan, Evaluasi, Pengendalian, dan Peningkatan; Determination, Planning, Implementation, Evaluation, Control, and Improvement) is carried out in practice, how organizational capacity affects the consistency of quality assurance, and how school actors contribute to the development of a quality culture. A qualitative research design was employed, using in depth interviews, observation, and document analysis as the primary sources of data. The findings reveal notable variation in the degree of SPMI internalization. While all schools have formally adopted the system, its effectiveness is shaped by human resource readiness, infrastructure availability, and managerial stability. Teachers hold a central role in sustaining learning quality, whereas administrative staff support the documentation and reporting of PPEPP processes. The involvement of school committees and industry partners strengthens accountability and aligns vocational learning with workforce needs. Despite these strengths, several challenges persist, including limited practical facilities and heavy administrative workloads that hinder the continuity of quality assurance activities The study concludes that SPMI functions not only as a technical mechanism but also as an integral component of public policy that requires institutional support, continuous professional development, and a sustained culture of quality at the school level. These findings suggest that improving the quality of vocational education calls for an integrated, collaborative, and data informed approach to managerial decision making.